Economic Analysis of Marginal Oil Field Development by Testing The Feasibility of GVM in Sharia Method Against NPV - Muhammad Ariyon; Ellyan Sastraningsih; Siti Nurhayati; Putri Rahmatillah (Scientific Contributions Oil and Gas, 2025)
A marginal oil field (MOF) is a field with relatively small hydrocarbon reserves located at significant depths. This presents major technical and economic challenges for its development. In the Central Sumatra Basin, a MOF with fair development potential has been discovered. The development of this MOF has to be analyzed to determine its feasibility. Previous research has predominantly evaluated oil field feasibility using conventional metrics, such as net present value (NPV) and profitability index (PI). However, assessing feasibility with a Syariah economic approach is an underdeveloped area of study. This study aims to compare conventional and Syariah methods for assessing MOF feasibility. The study involved field observation, primary and secondary data collection, calculation of reserves and oil production, cost estimation, oil price forecasting, and cash flow preparation based on a production sharing contract gross split contract scheme. The economic evaluation was conducted using conventional economic indicators (NPV, internal rate of return (IRR), payout time (POT), and PI) and Syariah indicators, namely, the gold value method (GVM) and gold index (GI). It is found that the development of the MOF is economically feasible. The NPV reached USD 172.27 million, with an IRR of 16.50%, a POT of 3.86 years, and a PI of 1.04. Moreover, the GVM was 10,687.03 grams of gold, and the GI stood at 1.20. This study demonstrates that the results of the Syariah method are consistent with those of the conventional methods, affirming its viability as an alternative evaluation approach for MOF development.